The Effect Of Entrepreneurial Capacity On The Welfare Of Cocoa Farmers In Kulon Progo Regency - Ayu Indah Lestari; Burhanuddin Burhanuddin; Rachmat Pambudy (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2026)
This study aims to explore the relationship between entrepreneurial capacity, business performance, and the welfare of cocoa farmers in Kulon Progo Regency. The research focuses on understanding how the entrepreneurial skills and business practices of cocoa farmers impact their economic well-being and productivity. This study uses a quantitative approach with a survey method and snowball sampling technique involving 178 respondents. Data were collected through interviews using a Likert scale-based questionnaire. Data analysis was performed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the relationship between latent variables. The results of the study indicate that entrepreneurial capacity has a positive and significant effect on business performance and farmer welfare. Business performance proved to be a mediating variable that strengthened the relationship between entrepreneurial capacity and farmers' welfare. Farmers who possess business management skills, good decision-making abilities, and strong cultivation practices are able to maintain an average land productivity of 7.74 tons per hectare, even though their land area is relatively small. The study also found that business diversification and employment outside the agricultural sector are important strategies for maintaining household economic resilience. Based on these findings, the study recommends that local governments and relevant stakeholders strengthen farmer institutions, provide access to capital, and develop marketing partnerships to ensure more stable and sustainable farmer incomes.